3D numerical simulation and structural behavior of reinforced concrete beams post-tensioned in the shear region - Kohnehpooshi, Omid; Jaafar, Mohd Saleh; Noorzaei, Jamaloddin; Muhammad Rashid, Raizal Saifulnaz (2010)
Aim of this work is to three dimensional finite element formulations of reinforced concrete beams to investigate the structural behavior of RC beams post-tensioned in the shear region. The concrete is modeled using twenty seven node lagrangian element. Bar and bond- slip between bar and concrete were modeled together by three dimensional truss-linkage elements. The steel plate which was implemented to transfer the post-tensioning force in shear region to the RC beam is modeled using 8 node isoparametric plate bending element with five DOF in each node. Several reinforced concrete beams have been modeled and analyzed for determining the variation of deflection, stresses, and slip between concrete and tendons. Study gives results on the effectiveness of post-tensioning in the shear region on structural behavior of reinforced concrete beams.